Gender-Based Oppression in Margaret Atwood's The Handmaid's Tale (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2024)
The perception of women as weak individuals results in their oppression, violence, and injustice, which are the fundamental reasons for their fight for equality, justice, and the right to be treated equally to men. The issue of women being objectified and abused by men is highlighted in the novel The Handmaid's Tale. This study aims to identify gender-based oppression against women and its impact on their social and mental well-being in the novel The Handmaid's Tale, using a qualitative descriptive method and a close reading approach to analyze literary motifs. The primary data source is the novel itself. The study utilized secondary sources such as journal articles, books, and relevant internet sources to gather data. The findings suggest that women experience various forms of oppression, including sexual harassment, gender role enforcement, objectification, and tight control by men. The impacts of this oppression result in trauma, psychological damage, internalization to survive, and loss of identity. In conclusion, gender-based oppression causes severe psychological and social agony for women.